Primary foreign languages national curriculum expectations in England: implications for practice from the Ofsted curriculum research review for languages and the 24 languages subject inspections - Malone, Elizabeth (Education 3-13, 2024)
This paper considers the implications for teachers and teaching of the Ofsted Curriculum Research Review for Languages [Ofsted. 2021. OCRR Series: Languages. Published 7 June 2021. Available online OCRR series: languages - GOV.UK ( www.gov.uk ). Accessed 8 June 2021.] (OCRR) and the content of 24 Languages Subject Inspections (LSI) in primary school foreign language provision carried out between October 2019 and March 2020. It illuminates practice by a single foreign language (FL) primary specialist. Her practice is compared and contrasted to the new Ofsted guidance and the National Curriculum requirements for English primary schools. This research adopts a phenomenological exploratory or discovery case study approach and data collection tools that respond to this overall design: Semi-structured interviews, informal conversations, emails, planning documentary analysis and a review of children's work. The findings show there are a myriad of factors which affect how languages are delivered in primary schools, including the number of language graduates, primary teachers' workloads and curriculum time. The paper concludes by considering the challenges that other teachers, not in the same situation as the FL teacher in this research, would have to overcome, without additional time or funding to also meet these requirements.